UNVEILING THE INFLUENCE OF VIRTUAL YOUTUBERS: HOW PARASOCIAL INTERACTION MEDIATES KOBO KANAERU’S INFLUENCE IN TOKOPEDIA’S MARKETING WAR CAMPAIGN - Ihsan, Mochammad Chairul; Rejito, Cattleya; Firmansyah, Wahyu Arif (Gapenas Publisher, 2025)
This study explores the role of Virtual YouTuber (VTuber) Kobo Kanaeru as an influencer marketer in Tokopedia’s WAR campaign and its impact on purchase intention, with parasocial interaction as a mediating variable. Utilizing the source credibility model (expertise, trustworthiness, attractiveness), we examine how these attributes influence purchase intention and the mediating effect of parasocial interaction. Employing a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data from 100 respondents aged 18–27 were analyzed. Results reveal that while expertise, trustworthiness, and attractiveness do not directly affect purchase intention, they significantly do so through parasocial interaction. This study contributes to the understanding of VTuber marketing as a growing trend in digital branding and highlights the importance of building strong virtual relationships with audiences